Impact of Poster-Based Counseling on Maternal Knowledge of High–Animal Protein Complementary Feeding among Toddlers Aged 6–24 Months - Saifa, Maritza; Arnisam, Arnisam (Jurusan Gizi, Poltekkes Kemenkes Aceh, 2025)
Stunting among toddlers remains a major nutritional problem in Indonesia, including Aceh Besar Regency. In Gampong Kayee Kunyet, Blang Bintang District, the prevalence of stunting reached 29.82% in 2024. One contributing factor is inadequate complementary feeding practices, particularly low intake of animal protein. Maternal knowledge plays an important role in shaping feeding practices and parenting behaviors. Nutrition counseling using poster media is considered an effective and easily understood educational approach. This study aimed to determine the effect of poster-based nutrition counseling on mothers’ knowledge of high–animal protein complementary feeding among toddlers aged 6–24 months at the integrated health post in Gampong Kayee Kunyet, Blang Bintang District, Aceh Besar Regency. This study employed a quasi-experimental design with a one-group pretest–posttest approach. The study population consisted of all mothers of toddlers aged 6–24 months attending the integrated health post (n = 21), using a total sampling technique. Data were analyzed using a dependent t-test with a 95% confidence level (α = 0.05) in SPSS. The mean knowledge score increased3 from 12.10 before the intervention to 15.86 after the intervention. Statistical analysis showed a significant difference (p = 0.000; p < 0.05), indicating a significant effect of the intervention. Poster-based nutrition counseling significantly improved mothers’ knowledge of high–animal protein complementary feeding. Health workers and community health cadres are encouraged to routinely use poster media and place them in strategic locations to improve accessibility for mothers of toddlers.